WINSTON-BATAN: A SEISMOLOGICAL GROUND-MOTION ANALYSIS CODE - Yuliastuti Yuliastuti; Euis Etty A; Topan Setiadipura (Universitas Syiah Kuala, 2018)
A thorough understanding of an earthquake is very important to provide a descriptive knowledge and in the same time as a prescriptive knowledge for the future development. In particular, it is essential for site selection and structural design development of nuclear reactor and other critical facilities. Ground motion acceleration time history is an important raw information to understand the earthquake and specific geological condition of where the data is recorded. This paper presented the development of strong-motion analysis code, called Winston-BATAN, which able to interpret ground motion time history. The analysis scope of the code including the ground motion parameters such as peak ground acceleration, several additional seismic intensity parameters, strong motion duration, its frequency content via Fast Fourier Transformation and response spectra analysis. Being developed based on an open source Python programming language, Winston-BATAN is flexible for exploratory study to exploit the ground motion time history and easily improve to accommodate additional features. This code able to read input from PEER NGA type file or a simple time and acceleration data type of ground motion. Analysis results of Winston-BATAN shows a very good agreement compare to the results from the standard tools Seismosignal® 2018 Software, in addition flexibility of this code, in particular, to explore the response spectra from the ground motion time history is demonstrated.